Influence of the association between simvastatin and demineralized bovine bone matrix on bone repair in rats - de Castro Lima, Carlos Eugênio Villaboim (2011)
Simvastatin, a drug used to lower blood cholesterol, has been reported to have an anabolic effect on bone. The purpose of this study was to evaluate the influence of simvastatin and demineralized bovine bone matrix (DBBM) on the repair of rat calvarial defects. Defects of 5 mm were created in 64 rats, divided into four groups: no local treatment (control); treatment with DBBM (DBBM); treatment with a combination of simvastatin solution (2.2 mg/50 μl) and DBBM (DBBMSIM-1); and treatment with simvastatin solution (0.5 mg/50 μl) and DBBM (DBBMSIM-2). Animals were sacrificed on postoperative day 30 or 60, after which the calvariae were X-rayed and prepared for histomorphometric evaluation. The data were submitted to statistical analysis (p < 0.05). Xrays revealed that, on postoperative day 30, animals treated with a lower dose of simvastatin presented the lowest bone density, whereas on postoperative day 60 the use of simvastatin, regardless of the dose, resulted in lower density than that observed in control and DBBM group samples. Histomorphometric analysis revealed that, on postoperative day 30, both DBBM and DBBMSIM-1 had a negative impact on bone formation. On postoperative day 60, none of the combinations tested impaired bone repair. These results showed that the association between DBBM and simvastatin had a negative impact on bone repair.